Las estrategias en la gestión del talento humano para el fortalecimiento de las competencias laborales (2020)
This work aims to determine how the principles and methodologies that allow training and certification based on labor competencies are applied, being an important and facilitating factor in companies in order to be competitive. Likewise, demonstrating how by applying strategies erroneously to develop the labor competencies in the officials’ does not guarantee the objective of committing the collaborators to carry out their functions, there are important factors such as experience, expertise and the development of their professional career and / or her daily activities is being the person herself who actively participates and the fundamental thing showing interest in her training.